(1329) An Economic Data Base in a Social Accounting Frame Work - khorshed, Motaz; Higazy, Osman (معهد التخطيط القومى, 2020)
The purpose of this paper is two fold. First to describe the design and management of a data base for the Egyptian economy. Second, to explain how to stared information I retrieved in a way to serve different modeling purposes. the purposed computer data system consists of a set of tables stored according to three levels of disaggregation. Three tables are linked together through computer programs which are used to assemble different Social Accounting Matrices (SAM). This modular design is justified from both technical and economic point of view. It permits the creation of a flexible data system with better space utilization and provides the necessary base for building various policy oriented SAM or any selected subset of them.